Agile HR: Fostering Innovation and Adaptability In Human Resource Practices - Hartanto Hartanto (Dinasti International Journal of Education Management And Social Science, 2024)
This paper provides a comprehensive literature review on Agile HR, examining its principles, implementation strategies, and benefits. The review highlights key agile principles such as iterative progress, continuous feedback, and cross-functional collaboration, which have been shown to enhance HR efficiency and employee engagement. Through the analysis of current research and case studies, this paper identifies significant gaps in the literature, particularly regarding the application of Agile HR in small and medium-sized enterprises (SMEs) and the long-term effects on organizational culture and employee retention. By addressing these gaps, this study aims to provide new insights into the strategic implementation of Agile HR practices. The findings suggest that Agile HR not only improves operational efficiency and workforce satisfaction but also fosters a more innovative and adaptable organizational culture. This review underscores the necessity for further empirical research to validate these benefits across diverse organizational settings and over extended periods. The paper concludes with recommendations for HR practitioners seeking to adopt agile methodologies, emphasizing the importance of a cultural shift, strong leadership, and continuous training to ensure successful implementation.